2021
DOI: 10.1177/0363546520981743
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anterolateral Structure Augmentation on the In Vivo Kinematics of Anterior Cruciate Ligament–Reconstructed Knees

Abstract: Background: Double-bundle anterior cruciate ligament (ACL) reconstruction (ACLR) is a well-known treatment that restores the stability of ACL-deficient knees. However, some isolated ACL-reconstructed knees ultimately show rotatory laxity and develop osteoarthritis. Whether combined ACLR with anterolateral structure (ALS) augmentation (ALSA) can provide better improvement in the in vivo knee rotational kinematics remains unknown. Hypothesis: When compared with isolated double-bundle ACLR, combined double-bundle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 77 publications
0
14
1
Order By: Relevance
“…The second point is the lack of presurgical kinematic data. Chen et al 3 claim that tibial medial translation could be potentially attributable to the potential lateral resistance of the LET on the lateral side of the knee; however, we disagree with this statement. Previous studies found a more medial tibial position in ACL-injured knees.…”
contrasting
confidence: 65%
See 3 more Smart Citations
“…The second point is the lack of presurgical kinematic data. Chen et al 3 claim that tibial medial translation could be potentially attributable to the potential lateral resistance of the LET on the lateral side of the knee; however, we disagree with this statement. Previous studies found a more medial tibial position in ACL-injured knees.…”
contrasting
confidence: 65%
“…Despite these considerations, we again congratulate Chen et al 3 for their valuable study that undoubtedly contributes to the recent literature about LET and permits us to debate such a key topic in sports medicine.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…We sincerely appreciate Agostinone et al’s insightful comments on our recent controlled laboratory study using the dual-fluoroscopic imaging tracking technique. Our study 7 finally included 15 patients to compare the in vivo kinematics between combined double-bundle anterior cruciate ligament reconstruction (ACLR) and anterolateral structure (ALS) augmentation (ALSA) and isolated double-bundle ACLR. We concluded that when compared with isolated double-bundle ACLR, double-bundle ACLR with ALSA resulted in anterolateral rotatory overconstraint during the lunge motion.…”
mentioning
confidence: 99%